Atherectomy using a solid‐state laser at 355 nm wavelength. Issue 10 (20th January 2017) - Herzog, Amir; Oszkinis, Grzegorz; Planer, David; Ziaja, Krzysztof; Kruszyna, Łukasz; Stanisić, Michał Goran; Ziaja, Damian; Ishaaya, Amiel A.; Kuczmik, Wacław
Abstract : Peripheral arterial disease (PAD), caused by atherosclerotic processes, is allied with an increased risk of ischemic events, limb loss, and death. Recently, the use of a solid‐state laser at 355 nm within a hybrid catheter was suggested for that purpose. In this work, short nanosecond pulses of a solid‐state laser at 355 nm delivered through a hybrid catheter, composed of optical fibers and a blunt mechanical blade, are used to conduct a pre‐clinical study and two clinical cases. The pre‐clinical study consisted of an atherosclerotic calcified cadaveric leg and a porcine in vivo trial within the iliac artery, respectively. The clinical cases include chronic total occlusions with a calcified lesion. The occluded cadaveric leg is recanalized successfully and no evidence of thermal necrosis is indicated in the histopathology analysis of the porcine study. No arterial wall damage is demonstrated on the animals' treated arteries and no significant impact on blood count and biochemistry analysis is noted in the animal trial. Successful recanalization of the occluded arteries followed by balloon angioplasty is obtained in both clinical cases. Our work constitutes a proof of concept for using a solid‐state pulsed laser at 355 nm in atherectomy. Abstract : Peripheral arterial disease (PAD) is allied with an increased risk of ischemic events and death. In this work, pulses of a solid‐state laser at 355 nm delivered through a hybrid catheter are used to conduct a pre‐clinical study and the first two clinical cases. Successful recanalization of calcified totally occluded arteries is obtained and constitutes a proof of concept for using a solid‐state pulsed laser at 355 nm in atherectomy.